Abdominal Pain in the Female Patient: A Case of Concurrent Acute Appendicitis and Ruptured Endometrioma. (20th December 2016) - Louis, Martine A.; Doubleday, Amanda R.; Lin, Elizabeth; Baek, Ji Yoon; Andoni, Alda; Wang, Xiao Hui
Abstract : General surgeons are often asked to evaluate acute abdominal pain which has an expanded differential diagnosis in women of childbearing age. Acute appendicitis accounts for many surgical emergencies as a common cause of nongynecologic pelvic pain. In some rare instances, acute appendicitis has been shown to occur simultaneously with a variety of gynecologic diseases. We report a case of concurrent acute appendicitis and ruptured ovarian endometrioma.